Monitoring futility and efficacy in phase II trials with Bayesian posterior distributions—A calibration approach. Issue 3 (2nd September 2018) - Kopp‐Schneider, Annette; Wiesenfarth, Manuel; Witt, Ruth; Edelmann, Dominic; Witt, Olaf; Abel, Ulrich
Abstract: A multistage single arm phase II trial with binary endpoint is considered. Bayesian posterior probabilities are used to monitor futility in interim analyses and efficacy in the final analysis. For a beta‐binomial model, decision rules based on Bayesian posterior probabilities are converted to "traditional" decision rules in terms of number of responders among patients observed so far. Analytical derivations are given for the probability of stopping for futility and for the probability to declare efficacy. A workflow is presented on how to select the parameters specifying the Bayesian design, and the operating characteristics of the design are investigated. It is outlined how the presented approach can be transferred to statistical models other than the beta‐binomial model.